Partitioning and separation of α-lactalbumin and β-lactoglobulin in polyethylene glycol/ammonium sulphate aqueous two-phase systems - Rodrigues, L. R. (2001)
The partition behaviour of α-lactalbumin (αla) and β-lactoglobulin (βlg) on PEG/(NH4)2SO4 system was studied. For purified proteins, a partition coefficient of 12.8 for αla and 0.34 for βlg, with mass recovery yields of 96.7% for αla in the upper phase and 83.8% for βlg in the lower phase was obtained, in 18% (w/w) PEG 900/14% (w/w) (NH4)2SO4 system, at pH 7. PEG/(NH4)2SO4 system was an economical alternative for the recovery and separation of the two proteins in cheese whey, allowing a 50% reduction in costs. An efficient and inexpensive separation of both proteins in cheese whey could be achieved, by using 16% (w/w) PEG 900/15% (w/w) (NH4)2SO4, at pH 7.5.